Between Spirituality and Accountability: The Dynamics of Friday Prayer Infaq at the Baitul Jannah Mosque from an Islamic Economic Perspective - Wenni Ristia Ulandari; Miti Yarmunida; Khairuddin Khairuddin; Ahmad Khoirudin Khoirudin; Liliany Purnama Ratu (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Objective: This study aims to analyze the factors influencing the Friday prayer infaq practice of Baitul Jannah Mosque worshippers from an Islamic economic perspective, focusing on the interaction between spiritual motivation, mosque management, and economic conditions. Design/Method/Approach: Using a qualitative approach with a descriptive case study design. Data were obtained through semi-structured interviews with six key informants (worshippers, mosque administrators, and religious leaders), and supported by observation and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing by triangulating sources for validity. Findings: The fluctuations in Friday prayer infaq are influenced by the economic instability experienced by some pilgrims, especially the young age group. The principle of hifz al-mal (safeguarding wealth) is often more dominant than spiritual motivation, so infaq is seen as the allocation of residual income. Conventional financial reporting has not been fully able to reach pilgrims who rarely attend and the digital generation, and the allocation of funds oriented to physical operations reduces the optimization of social benefits of community empowerment. Originality/Value: This research contributes to the study of mosque management and Islamic philanthropy by revealing the dynamics of infaq behavior in low-income housing communities. The findings show that strengthening digital-based transparency and the development of community economic empowerment programs have the potential to increase infaq participation by bridging the gap between spiritual values and the economic reality of pilgrims.